Circular RNA circZNF652 is overexpressed in osteoarthritis and positively regulates LPS-induced apoptosis of chondrocytes by upregulating PTEN. (3rd October 2021) - Yuan, Xuefeng; Zhang, Yingchi; Cai, Cong; Liu, Chaoxu; Xie, Jie; Yi, Chengla
Abstract: Circular RNA circZNF652 promotes LPS-induced inflammation, contributing to the development of osteoarthritis (OA), indicating the potential involvement of circZNF652 in OA. This study was carried to explore the involvement of circZNF652 in OA. RT-qPCR was performed to analyse the expression of circZNF652 and PTEN mRNA in synovial fluid samples from 60 OA patients and 60 healthy controls. Correlations between circZNF652 and PTEN mRNA were analysed by Pearson's correlation coefficient. Overexpression and siRNA silencing of circZNF652 were achieved in chondrocytes, followed by performing RT-qPCR and Western blot to analyse the expression of PTEN. The role of circZNF652 and PTEN in regulating the apoptosis of chondrocytes induced by LPS was analysed by cell apoptosis assay. We found that circZNF652 was overexpressed in OA and positively correlated with PTEN, MMP13, and NF-KB mRNA. In chondrocytes, circZNF652 overexpression increased the expression of PTEN, MMP13, and NF-KB; circZNF652 siRNA silencing decreased the expression of PTEN, MMP13, and NF-KB. Moreover, circZNF652 and PTEN positively regulated the apoptosis of chondrocytes induced by LPS. PTEN overexpression reversed the inhibitory effects of circZNF652 siRNA silencing on cell apoptosis. Therefore, circZNF652 is overexpressed in OA and positively regulates LPS-induced apoptosis of chondrocytes by upregulating PTEN.